Tehno in subjekt - Anđelković, Bojan (Monitor ISH, 2007)
Contemporary philosophical theories associate the emergence of the Cartesian subject with the birth of modern science. On the other hand, considering that science is evolving into techno-science in a number of fields, such theories surprisingly fail to inquire directly into the influence of the - new - technologies on the subject. This inquiry is the topic of the present paper, with an exploration of what happens to the members of techno culture attending a party. With the help of various technologies, the subjects are first brought to a point close to zero. This condition is essential for the second phase, the formation of a multiple subject, which is not merely human, but technological as well. Another question addressed is whether such a subject can be political.
Keywords: technology; tehnologija; subjekt; filozofija; philosophy; sodobna filozofija; tehnokultura